Teacher Performance of the Public Junior High School in North Padang Subdistrict - Jesica Zulianda; Anisah Anisah; Nurhizrah Gistitusti; Yulisanto Santoso (Universitas Negeri Padang, 2022)
This exploration was completed at the State Junior High School, Padang Utara District, for getting a data about educator's exhibitions. This sort of examination is distinct with a quantitative methodology. The information examination procedure utilizes the mean equation. The populace in this examination was all educators who instructed at the Padang Utara District State Junior High School which added up to 108 instructors, and the example was drawn in by utilizing the Proportionate Stratified Random Sampling Technique which added up to 57 educators. The instrument for the exploration is a poll with a likert scale model. The survey utilized has been tried for approval and unwavering quality utilizing with SPSS application variant 16.0. The aftereffects of the information handling outline that (1) the typical score for abilities is 4,497 and the classification is great, (2) the typical score for work exactness is 4,307 and the class is great, (3) the typical score for collaboration is 4,568 and the class is brilliant, and (4) the typical score for imagination is 4,409 and the class is great. In general, the presentation of educators at the Padang Utara District State Junior High School is getting in the high class with a typical score of 4,445Keywords: Teachers Performance